Community-based Tourism Management Agricultural Tourism Development Tai Lue Community, Pua District, Nan Province - Tachom, Charasnan; Rinpanussak, Narin; Suprakarn, Yuttapum (Journal of Thammawat, 2022)
Research paper on Community-based tourism management, the development of agricultural tourism in Tai Lue community, Pua district, Nan province It is a participatory action research study. And the population survey research of Tai Lue cultural community in Pua district by using the Chain or snow Brainstorming from group interviews using tools And the Tai Lue village community meeting Distributed throughout the Doi Phu Kha valley plain in the development of tourism management by the Tai Lue community There were results for organizing a forum for the development of agricultural tourism of the Tai Lue community, Pua District, Nan Province, with objectives: 1. To study the situation and assess the potential of community tourism management in Pua District. Case studies of community-based tourism management2. Development of Thai Lue community tourism Agricultural Tourism Development, Tai Lue Community, Pua District, Nan Province